Transposição de solo para restauração de área degradada no núcleo de desertificação do Seridó, na Paraíba - Sousa, Flaubert Queiroga de (2017)
The desertification phenomenon is the process of environmental degradation of arid, semi-arid and dry sub-humid lands, caused by natural factors and anthropic actions. In the Seridó Desertification Nucleus, specifically in the State of Paraíba, the delimited area with high level of degradation covers the municipalities of Santa Luzia and Várzea, and the desertification in this nucleus is particularly related to climatic factors, pedogenetic processes and anthropic interventions. In the light of these considerations, ecological restoration arises as a viable alternative to recover the lost environmental services gone with the degradation. Among the different kinds of restoration models used in Brazil, nucleation is nowadays one of the most widespread. It consists of the use of several techniques that, together, make the natural process of succession easier. One of these techniques, the transposition of soil portions (nuclei), consists of removing the topsoil from the litterer soil layer to a degraded area. Based on it, this research mainly aims to evaluate the possible recovering of a degraded area in the Seridó Desertification Nucleus using the technique of soil transposition (topsoil). In order to do so, through soil quality bioindicators (soil seed bank, edaphic respiration and soil mesofauna) potentialities for ecological restoration of several kinds of soil were evaluated. Seven areas of different microregions of Paraíba semi-arid were selected for the soil transposition, and its allocation in a degraded area. The outlining was in a randomized block, consisting of eight treatments, one for the Control (degraded area) and the other seven for the soil transported from areas preserved in the microregions. Monthly, the soil seed bank, edaphic respiration and soil mesofauna analyzes were performed. The transposition of the soils brought a new seed bank to the area under study, which facilitated the rise of new species. The edaphic respiration and the mesofauna in most transported soils were greater than those in the degraded area. The technique of soil transposition from the several microregions is a viable alternative to stimulate forest succession in degraded areas that cover Seridó Desertification Nucleus.